Use of the Atlantic nut clam (Nucula proxima) and catworm (Nephtys incisa) in a sentinel species approach for monitoring the health of Bay of Fundy estuaries. Issue 1 (15th May 2016) - Pippy, B.A.; Kidd, K.A.; Munkittrick, K.R.; Mercer, A.; Hunt, H.
Abstract: Designing an effective environmental monitoring system for population responses requires knowledge of the biology of appropriate sentinel species and baseline information on the area's physical and chemical characteristics. This study collected information in Saint John Harbor, NB, Canada, for two abundant marine benthic invertebrates, the Atlantic nut clam ( Nucula proxima ) and the catworm ( Nephtys incisa ) to characterize their seasonal and spatial variability, determine the ideal sampling time and methods, and develop baseline data for future studies. We also evaluated whether contamination is impacting invertebrates by comparing sediment metal concentrations to responses of benthic infauna. Metals were generally below sediment quality guidelines except for nickel and arsenic. Clam densities were variable between sites but not seasons, whereas catworm densities were not significantly different between sites or seasons. Overall, these species show potential for environmental monitoring, although investigation at more contaminated sites is warranted to assess their sensitivity. Highlights: We studied Nucula proxima and Nephtys incisa as novel sentinel species. These species have not been considered before as sentinels, or studied in detail. We measured population responses in infauna and sediment contaminant concentrations. Metal and PAH concentrations were generally low in the sediment. Size and abundance of invertebrates varied between locations and sampling times.